Art, cultural heritage and the market : ethical and legal issues - Vadi, Valentina; Schneider, Hildegard (Heidelberg : Springer, 2014)
In the age of economic globalisation, do art and heritage matter? Once the domain of elitist practitioners and scholars, the governance of cultural heritage and the destiny of iconic artefacts have emerged as the new frontier of international law, making headlines and attracting the varied interests of academics and policy-makers, museum curators and collectors, human rights activists and investment lawyers, and artists and economists, just to mention a few. The return of cultural artefacts to their legitimate owners, the recovery of underwater cultural heritage, and the protection and promotion of artistic expressions are just some of the pressing issues addressed by this book. Contemporary intersections between art, cultural heritage and the market are complicated by a variety of ethical and legal issues, which often describe complex global relations. Should works of art be treated differently from other goods? What happens if a work of art, currently exhibited in a museum, turns out to have been looted? What is the relevant legal framework? What should be done with ancient shipwrecks filled with objects from former colonies? Should such objects be kept by the finders? Should they be returned to the country of origin? This book addresses these different questions while highlighting the complex interplay between legal and ethical issues in the context of cultural governance. The approach is mainly legal, but interdisciplinary aspects are considered as well.
Art, cultural heritage and the market : legal and ethical issues / V. Vadi and H. Schneider -- Reparation art : finding common ground in the resolution of disputes on Russian war spoils and Nazi-looted art / Anne Laure Bandle and Raphael Contel -- Alternative dispute resolution in restitution claims and the binding expert opinion procedure of the Dutch restitutions committee / Evelien Campfens -- Alternative dispute resolution mechanisms in cultural property related disputes : UNESCO mediation and conciliation procedures / Sabrina Urbinati -- Protecting cultural objects : enforcing the illicit export of foreign cultural objects / Sophie Vigneron -- The perils of buying and selling art at the fair : legal issues in title / Judith B. Prowda -- How to break the deadlock in the debate about colonial acquisitions? / Jos van Beurden -- Repatriation and multilevel heritage legislation in Canada and Australia : a comparative analysis of the challenges in repatriating religious artefacts to indigenous communities / Vanessa M. Tuensmeyer -- The underwater heritage of the Riace bronzes : ethics, provenance and the art market in Ancient Rome and today / David Bellingham -- Underwater cultural heritage and the market : the uncertain destiny of historic sunken warships under international law / Valentina Vadi -- Collectible : the social and ethical implications surrounding the collected object / Sophie Kromholz -- The art of the sale : museums and deaccessioning / Robert K. Paterson -- The resale right directive : a comparative analysis of its implementation in Germany and the United Kingdom / Maximilian Gaber -- Art exchange? : how the international art market lacks a clear regulatory framework / Jason-Louise Graham.
Includes bibliographical references and index.
Keywords: Cultural property -- Protection -- Law and legislation; Law and art; Museums -- Acquisitions; Museums -- Law and legislation